THE INFLUENCE OF COLLEGE LECTURER'S LEADERSHIP STYLE ON STUDENT'S ACADEMIC ACHIEVEMENT - Lisa Sarinah (Jurnal Ekonomi, 2022)
The purpose of this research is to investigate whether or not there is a connection between how university professors at the Faculty of Economics and Business at the National University lead their classes and their students' academic success. Taking a descriptive and non-experimental method, we conducted a cross-sectional study with a sample size of twelve lecturers. We analyzed our data with the assistance of SPSS utilizing Pearson correlation and the regression coefficient. The findings indicate that there is a statistically significant positive correlation between the laissez-faire leadership style and the mean score that a group of students studying the subject attained (0.647 *), and the regression coefficient is 40.1% below the reliability threshold for 95% of the time. The student who completed the semester course (Design) with the most excellent grade point average correlates with a teacher whose leadership style is a combination of authoritarian, laissez-faire, and transactional approaches (17.8 points).